Efektivitas Penggunaan Media Interaktif Berbantuan Quizizz Paper Mode Terhadap Hasil Belajar Siswa pada Mata Pelajaran Tematik Kelas IV SD Sederajat - Sandria, Detriana; Yusri, Meldi Ade Kurnia; Hidayati, Abna; Rahmi, Ulfia (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the effectiveness of interactive media assisted by quizizz paper mode on student learning outcomes in Thematic Subjects in grade IV elementary school equivalent. This study uses a quantitative approach with the Quasy Experiment type of research. The design of this study uses a type of one group pretest-posttest design. The population in this study is grade IV elementary school students equivalent to sampling using the Purposive Sampling technique. At SDN 01 Koto Tangah Simalanggang with a total of 20 students. The data collection technique is carried out by, namely first conducting an initial test, providing treatment, final test and documentation. The data analysis technique was carried out by comparing pretest and posttest scores using the Wilcoxon Test. The results of the study showed an average score of 70.55 for the pretest while an average score of 83.9 for the posttest. So the data obtained will be analyzed using the Wilcoxon test with decision making if the value of Asymp.sig < 0.05, then the hypothesis is accepted, if the value of Asymp.Sig > 0.05, then the hypothesis is rejected.  Based on the output of "Test Statistics", it is known that Asymp.Sig (2-tailed) is worth 0.000. Because the value of 0.000 < 0.05 can be concluded that "Hypothesis Accepted" means that there is a difference between the learning outcomes for the pretest and posttest. So it can be concluded that the use of interactive media assisted by paper mode is effective in improving student learning outcomes